2003
DOI: 10.1007/bf03033156
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone down-regulates dopamine D4 receptor in a mouse cerebral cortex neuronal cell line

Abstract: We have previously reported that restraint stress applied to the gestant mother results in long-lasting effects in the offspring that show an increase in the number of dopamine D2-type receptors in limbic areas on the adult rat brain cortex. Evidence that stress during pregnancy results in activation of the hypothalamic-pituitary-adrenal (HPA) axis has been extensively demonstrated. Therefore, high levels of corticosterone secreted in response to stress by the gestant mother might be one of the predisposing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Another hypothesis suggested that prenatal stress‐induced corticosterone secretion can act directly alter dopamine receptors (Lammers et al, 1999). However, our recent results showed that corticosterone inhibited D 4 receptor (member of the DA D 2 ‐like receptors) expression in immortalized cell lines from cerebral cortex of normal mouse fetuses (Barros et al, 2003), suggesting that overexpression of DA D 2 receptors in prenatally stressed offspring is not directly promoted by corticosterone.…”
Section: Discussionmentioning
confidence: 94%
“…Another hypothesis suggested that prenatal stress‐induced corticosterone secretion can act directly alter dopamine receptors (Lammers et al, 1999). However, our recent results showed that corticosterone inhibited D 4 receptor (member of the DA D 2 ‐like receptors) expression in immortalized cell lines from cerebral cortex of normal mouse fetuses (Barros et al, 2003), suggesting that overexpression of DA D 2 receptors in prenatally stressed offspring is not directly promoted by corticosterone.…”
Section: Discussionmentioning
confidence: 94%
“…The existing data on ADHD suggest that alterations in dopaminergic signaling due to pyrethroid insecticide exposure influences ADHD pathogenesis and are important for studying ADHD risk [41,51]. Chronic stress exposure also alters the dopamine system and could further potentiate the risk of ADHD [60,87,94,95,96]. Given the independent effects of pyrethroid insecticides and chronic stress on the dopamine system, we hypothesized that combined pyrethroid insecticide and stress hormone exposure during critical periods of neurodevelopment would additively alter protein expression and the function of key components of the dopamine system, thereby further increasing the risk of developing ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Drd4 was reduced by CORT treatment in a neuronal cell line (Barros et al, 2003). However, how Drd4 expression was impeded by stress exposure and the resultant elevation of CORT levels remained unknown thus far.…”
Section: Npas4-drd4 Axis Controlled By Cortmentioning
confidence: 99%